(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study was conducted to ascertain curriculum contents of entrepreneurship education which are suitable and teaching methods/strategies that are effective for producing capable entrepreneurs in tertiary institutions in Anambra state. A questionnaire was used to collect data from 42 business educators who teach entrepreneurship education courses. Two research questions and two hypothesis guided the study. Mean was used to answer the research questions, while t-test and ANOVA were used to test the hypotheses. The findings of the study indicated that business educators’ in tertiary institutions in Anambra state perceived the curriculum content’ of entrepreneurship education to be suitable for producing capable entrepreneurs, and the teaching methods/strategies as effective except for lecture method. It was therefore recommended among others that business educators should adopt hands-on practical approach in teaching entrepreneurship education courses.